In situ cross-linked nonaqueous polymer electrolyte for zinc-metal polymer batteries and hybrid supercapacitors - Vijayakumar, Vidyanand; Ghosh, Meena; Kurian, Maria; Torris, Arun; Dilwale, Swati; Badiger, V. Manohar; Winter, Martin; Nair, Jijeesh Ravi; Kurungot, Sreekumar (Small, 2020)
This work reports the facile synthesis of nonaqueous zinc-ion conducting polymer electrolyte (ZIP) membranes using an ultraviolet (UV)-light-induced photopolymerization technique, with room temperature (RT) ionic conductivity values in the order of 10(-3)S cm(-1). The ZIP membranes demonstrate excellent physicochemical and electrochemical properties, including an electrochemical stability window of >2.4 V versus Zn|Zn(2+)and dendrite-free plating/stripping processes in symmetric Zn||Zn cells. Besides, a UV-polymerization-assisted in situ process is developed to produce ZIP (abbreviated i-ZIP), which is adopted for the first time to fabricate a nonaqueous zinc-metal polymer battery (ZMPB; VOPO4|i-ZIP|Zn) and zinc-metal hybrid polymer supercapacitor (ZMPS; activated carbon|i-ZIP|Zn) cells. The VOPO(4)cathode employed in ZMPB possesses a layered morphology, exhibiting a high average operating voltage of approximate to 1.2 V. As compared to the conventional polymer cell assembling approach using the ex situ process, the in situ process is simple and it enhances the overall electrochemical performance, which enables the widespread intrusion of ZMPBs and ZMPSs into the application domain. Indeed, considering the promising aspects of the proposed ZIP and its easy processability, this work opens up a new direction for the emergence of the zinc-based energy storage technologies.
Keywords: nonaqueous electrolytes; polymer electrolytes; postlithium batteries; Supercapacitors; zinc-metal batteries